Important ecosystem function, low redundancy and high vulnerability: The trifecta argument for protecting the Great Barrier Reef's tabular Acropora. Issue 5 (1st June 2021) - Ortiz, Juan C.; Pears, Rachel J.; Beeden, Roger; Dryden, Jen; Wolff, Nicholas H.; Gomez Cabrera, Maria del C.; Mumby, Peter J
Abstract: Identifying organisms that play an important role in maintaining ecosystem function is a key aspect of resilience‐based management. For Australia's Great Barrier Reef (GBR), we found that the recovery ability of shallow exposed fore‐reefs is more than 14 times higher when tabular Acropora are present. The disproportionate role that tabular Acropora play appears to be driven by a combination of traits including high recruitment, high growth rate and, importantly, large maximum colony sizes. Despite this key role, tabular Acropora are highly sensitive to most pressures. We compile evidence suggesting that if tabular corals were to decline or disappear on the GBR, the potential for reef recovery on exposed fore‐reefs would be considerably slowed. We then consider the merits of placing special emphasis on the protection of tabular Acropora within the management of the GBR. Importantly, we recognise that an analysis of costs and benefits of such recognition is vital before any change is implemented. Actions might include targeted crown‐of‐thorns starfish control, anchoring restrictions and protection for tabular corals on reefs identified as essential for their larval dispersal. In addition, targeted communications about the critical importance of these highly recognisable corals may boost community support and participation in their protection.